2019
DOI: 10.1016/j.clnu.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Home parenteral nutrition increases fat free mass in patients with incurable gastrointestinal cancer. Results of a randomized controlled trial

Abstract: (NCT02066363) www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 45 publications
2
83
0
3
Order By: Relevance
“…For ethical reasons the benefit of HPN has not been investigated in RCTs. However, over the last ten years several prospective and retrospective observational studies in advanced cancer patients with inadequate oral intake receiving chemoradiotherapy showed that HPN improves QoL [48][49][50][51][52][53][54] and prolongs survival [46,[55][56][57][58].…”
Section: Parenteral Nutritionmentioning
confidence: 99%
“…For ethical reasons the benefit of HPN has not been investigated in RCTs. However, over the last ten years several prospective and retrospective observational studies in advanced cancer patients with inadequate oral intake receiving chemoradiotherapy showed that HPN improves QoL [48][49][50][51][52][53][54] and prolongs survival [46,[55][56][57][58].…”
Section: Parenteral Nutritionmentioning
confidence: 99%
“…Data were analysed from a prospective cohort of patients with incurable gastrointestinal cancer who were consecutively screened and offered participation in a RCT [17]. Patients were recruited in relation to the clinical randomized study of parenteral nutrition, in which they declined to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Results from the RCT were not the scope of this work, and therefore these data are reported elsewhere [17].…”
Section: Methodsmentioning
confidence: 99%
“…Cancer‐related cachexia is not reversible by conventional oral nutritional support . Parenteral nutrition and supplementation with branched chain amino acids and fish oil have shown promising results in preserving muscle mass loss in patients at risk for developing cachexia . Interventions to increase amino acid ingestions to promote protein synthesis in patients diagnosed with cachexia have shown conflicting results .…”
Section: Exercise and Nutritional Interventionsmentioning
confidence: 99%